PREDIKSI INDEKS PERFORMA SISWA BERDASARKAN WAKTU BELAJAR, NILAI SEBELUMNYA, KEGIATAN EKSTRAKURIKULER, WAKTU TIDUR, DAN BANYAKNYA SOAL YANG DIKERJAKAN DENGAN REGRESI LINEAR KUADRAT-TERKECIL: Prediction of Student Performance Index Based on Hours Studied, Previous Scores, Extracurricular Activities, Sleep Hours, and Sample Question Papers Practiced with Least-Squares Linear Regression - Handoyo, Sapto Mukti; Najib, Mohamad Khoirun (Yayasan Al-Amin Qalbu, 2025)
The students’ performance index is a measure used to represent the overall performance of students. One model that can be used to predict the students’ performance index is a machine learning-based regression model. Therefore, this study aims to apply a machine learning-based least-squares linear regression model to predict the performance index using these factors and interpret the model. The regression model utilized is available in the Julia programming package called MLJ. This model is evaluated based on several criteria, including R-squared, RMSE, and MAE. The results show that the previous scores have the most significant influence on the students’ performance index. Furthermore, the R-squared value for the test data is 0.988, the RMSE for the training data is 0.106, the RMSE for the test data is 0.108, the MAE for the training data is 0.84, and the MAE for the test data is 0.86. Based on the evaluation results, the model has good predictive performance with low average error, does not experience overfitting, and has good generalization ability.